Traits linked to sensory processing sensitivity mediate the relationship between externally oriented thinking and fantasizing - Jakobson, Lorna S.; McQuarrie, Amanda M.; Van Landeghem, Chantal; Smith, Stephen D. (Frontiers in Psychology, 2024)
Introduction Alexithymia is characterized by difficulties identifying and describing feelings but expression of externally oriented thinking (EOT) and difficulty fantasizing is more variable. In two studies, we investigated whether links between EOT and fantasizing are mediated by sensory processing sensitivity (SPS). Methods University students completed measures of alexithymia, SPS, and fantasizing. Results In Study 1 (N = 700) we identified two clusters of SPS traits: a positive facet (sensitivity to subtle stimuli) and a negative facet (sensitivity to uncomfortable stimuli). In the 499 participants who completed the fantasy measure, low EOT scores predicted stronger SPS positive and negative traits, which predicted a stronger tendency to mentally project oneself into the lives of characters in books, movies, and plays. In Study 2 (N = 600), the link between EOT and this same fantasizing tendency was again mediated by features of SPS—in this case fantasy proneness and emotional reactivity. Discussion We suggest that, whereas individuals who score high on EOT have an impoverished fantasy life, those who score relatively low on EOT and turn their attention inward are able to maintain stronger representations of imagined events in working memory (enhancing the likelihood that they will be recalled) and react more strongly to these events (enhancing their salience). Stronger expression of these features of SPS, in turn, increases the likelihood that one will develop a cognitive style that involves the application of imagery-based strategies to support deep processing of the thoughts and feelings of characters depicted in narratives.